Designer Dual Therapy Nanolayered Implant Coatings Eradicate Biofilms and Accelerate Bone Tissue Repair - Min, Jouha (ACS Nano, 2016)
Infections associated with orthopedic implants cause increased morbidity and significant healthcare cost. A prolonged and expensive two-stage procedure requiring two surgical steps and a 6–8 week period of joint immobilization exists as today’s gold standard for the revision arthroplasty of an infected prosthesis. Because infection is much more common in implant replacement surgeries, these issues greatly impact long-term patient care for a continually growing part of the population. Here, we demonstrate that a single-stage revision using prostheses coated with self-assembled, hydrolytically degradable multilayers that sequentially deliver the antibiotic (gentamicin) and the osteoinductive growth factor (BMP-2) in a time-staggered manner enables both eradication of established biofilms and complete and rapid bone tissue repair around the implant in rats with induced osteomyelitis. The nanolayered construct allows precise independent control of release kinetics and loading for each therapeutic agent in an infected implant environment. Antibiotics contained in top layers can be tuned to provide a rapid release at early times sufficient to eliminate infection, followed by sustained release for several weeks, and the underlying BMP-2 component enables a long-term sustained release of BMP-2, which induced more significant and mechanically competent bone formation than a short-term burst release. The successful growth factor-mediated osteointegration of the multilayered implants with the host tissue improved bone-implant interfacial strength 15-fold when compared with the uncoated one. These findings demonstrate the potential of this layered release strategy to introduce a durable next-generation implant solution, ultimately an important step forward to future large animal models toward the clinic.